Effect of chewing an apple on dental plaque removal and on salivary bacterial viability. - Susana Rubido; Lucía García-Caballero; María Teresa Abeleira; Jacobo Limeres; Marta García; Pedro Diz (PLoS ONE)
Objectives Studies on dental plaque removal by chewing an apple are scarce and dated, with conflicting findings. This study aimed to determine whether chewing an apple produced mechanical removal of dental plaque or had any effect on salivary bacterial viability. Methods The study group consisted of 20 healthy adults with good oral health status who were randomly assigned to brush their teeth or eat an apple. After 2 weeks, the experiment was repeated with the order reversed. Plaque index (PI) and the bacterial viability (BV) in a sample of whole saliva (spit) were determined before brushing or apple eating (baseline, B), immediately afterward (A) and 24 hours afterward (24). Results After chewing an apple, PI-A was significantly higher than both PI-B (P < .001) and PI-24 (P < .001). BV-A was significantly lower than BV-B (P < .001), with a return to baseline values at the BV-24 measurement. Conclusions Chewing an apple does not remove dental plaque, and may favor plaque regrowth during the first 24 hours, but it does produce an immediate reduction in salivary bacterial viability similar to that after tooth brushing.